Beyond the "zaman kaset" (era of the cassette); Interview with Euis Komariah - Spiller, Henry (Wacana, Journal of the Humanities of Indonesia, 2025)
Indonesian music fans all over the world were saddened to learn of the untimely death of Euis Komariah on 11 August 2011, in Bandung, West Java. Ibu Euis earned international fame as an award-winning singer, a teacher, and a businesswoman. I had the opportunity to interview her about her illustrious career on 19 April 2007, during her residency at the University of California, Davis. This essay provides an annotated translation of that interview, in which we addressed topics including media (radio broadcasting and the cassette industry), recording technologies, the development of new tunings and modes, and the development of jaipongan. The annotations expand on the interview’s very particular historical context of the 2007 music scene and contextualize it in terms of more recent developments in Sundanese music and media. It is my intention that this record of our conversation will disseminate some of the details of this remarkable artist’s life and career to a wide audience, and contribute to her lasting memory, both in Indonesia and abroad, as well as provide a broader context for understanding contemporary Sundanese music.